2017
DOI: 10.3892/ijmm.2017.2967
|View full text |Cite
|
Sign up to set email alerts
|

Blood glycemia-modulating effects of melanian snail protein hydrolysates in mice with type II diabetes

Abstract: Abstract. Freshwater animal proteins have long been used as nutrient supplements. In this study, melanian snail (Semisulcospira libertina) protein hydrolysates (MPh) were found to exert anti-diabetic and protective effects against liver and kidney damage in mice with type II diabetes adapted to a 45% kcal high-fat diet (HFD). The hypoglycemic, hepatoprotective and nephroprotective effects of MPh were analyzed after 12 weeks of the continuous oral administration of MPh at 125, 250 and 500 mg/kg. Diabetic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(64 citation statements)
references
References 77 publications
3
20
0
Order By: Relevance
“…The 50 mg/kg WL also elevated the modulation of pancreatic lipid enzyme and activation of antioxidant defense system compared to metformin 250 mg/kg ( Figure 10). An increase in the deposit of adipose tissue is a general aspect of obesity [13,14,16,31]. Adipose tissue acts as an energy storage organ, as well as an endocrine and secretory organ [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 50 mg/kg WL also elevated the modulation of pancreatic lipid enzyme and activation of antioxidant defense system compared to metformin 250 mg/kg ( Figure 10). An increase in the deposit of adipose tissue is a general aspect of obesity [13,14,16,31]. Adipose tissue acts as an energy storage organ, as well as an endocrine and secretory organ [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is the key cause and symptom of diabetes; this parameter should be regulated to treat diabetes [13,16]. HFD-fed mice have been wildly employed to study for type II diabetes; they have been shown to develop noticeable hyperglycemia [13,14,29,31]. As insulin resistance progresses to type II diabetes, enhanced levels in blood insulin and Hb1Ac have been detected after chronic intake of an HFD [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences were considered significant at p < 0.05. In addition, the percent changes between intact vehicle and OVA control mice were calculated to monitor the severities of asthmatic changes induced by OVA sensitization and boosting, and the percent changes between OVA control mice and PS + CR 300 and 1,000 mg/kg or DEXA 3 mg/kg treated mice were also calculated to help us understand the efficacy, according to our previous reports [31,32] as follows:…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the percentage changes compared with the HFD control were estimated to improve understanding of the efficacy of the test substances. The percentage changes between the HFD and intact control groups were also determined to detect the induction of disease using the following equations in accordance with our previous studies ( 19 , 50 ).…”
Section: Methodsmentioning
confidence: 99%